Question
upstudy study bank question image url

Given \[ x^{2}+(k-1) x=-k+2 \] Show that the roots are real and rational for all

Ask by Reyes Cross. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The roots of the equation \(x^{2}+(k-1)x=-k+2\) are real and rational for all values of \(k\).

Solution

Solve the equation \( x^{2}+(k-1)x=-k+2 \). Solve the equation by following steps: - step0: Solve for \(x\): \(x^{2}+\left(k-1\right)x=-k+2\) - step1: Move the expression to the left side: \(x^{2}+\left(k-1\right)x-\left(-k+2\right)=0\) - step2: Remove the parentheses: \(x^{2}+\left(k-1\right)x+k-2=0\) - step3: Expand the expression: \(x^{2}+kx-x+k-2=0\) - step4: Factor the expression: \(\left(x+k-2\right)\left(x+1\right)=0\) - step5: Separate into possible cases: \(\begin{align}&x+k-2=0\\&x+1=0\end{align}\) - step6: Solve the equation: \(\begin{align}&x=-k+2\\&x=-1\end{align}\) The roots of the equation \(x^{2}+(k-1)x=-k+2\) are \(x=-k+2\) and \(x=-1\). To show that the roots are real and rational for all values of \(k\), we need to analyze the nature of the roots. 1. Real roots: The roots are real because they are in the form of \(x=a\) and \(x=b\), where \(a\) and \(b\) are real numbers. 2. Rational roots: The roots are rational because they are in the form of \(x=\frac{p}{q}\), where \(p\) and \(q\) are integers and \(q \neq 0\). In this case, the roots are \(x=-k+2\) and \(x=-1\), which are rational for all values of \(k\). Therefore, the roots of the equation \(x^{2}+(k-1)x=-k+2\) are real and rational for all values of \(k\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To determine if the roots of the quadratic equation \[ x^{2}+(k-1)x + (k-2) = 0 \] are real and rational for all values of \( k \), we can examine the discriminant, \( D \), defined as \[ D = b^2 - 4ac \] where \( a = 1 \), \( b = k - 1 \), and \( c = k - 2 \). Substituting these values in, we get: \[ D = (k-1)^2 - 4 \cdot 1 \cdot (k - 2) \] Calculating the discriminant: \[ D = (k-1)^2 - 4(k - 2) = (k^2 - 2k + 1) - (4k - 8) = k^2 - 2k + 1 - 4k + 8 = k^2 - 6k + 9 \] This simplifies to \[ D = (k-3)^2 \] Since the square of any real number is always non-negative, \( D \geq 0 \). Thus, the roots are indeed real for all values of \( k \). Next, we need to check if the roots are rational. For the roots to be rational, the discriminant \( D \) must be a perfect square. Since \( D = (k-3)^2 \) is always a square (being the square of \( k-3 \)), the roots will be rational for all values of \( k \). In conclusion, the roots of the equation \( x^{2}+(k-1)x + (k-2) = 0 \) are real and rational for all \( k \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy